3x-6x+6=x-5+11

Simple and best practice solution for 3x-6x+6=x-5+11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-6x+6=x-5+11 equation:


Simplifying
3x + -6x + 6 = x + -5 + 11

Reorder the terms:
6 + 3x + -6x = x + -5 + 11

Combine like terms: 3x + -6x = -3x
6 + -3x = x + -5 + 11

Reorder the terms:
6 + -3x = -5 + 11 + x

Combine like terms: -5 + 11 = 6
6 + -3x = 6 + x

Add '-6' to each side of the equation.
6 + -6 + -3x = 6 + -6 + x

Combine like terms: 6 + -6 = 0
0 + -3x = 6 + -6 + x
-3x = 6 + -6 + x

Combine like terms: 6 + -6 = 0
-3x = 0 + x
-3x = x

Solving
-3x = x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
-3x + -1x = x + -1x

Combine like terms: -3x + -1x = -4x
-4x = x + -1x

Combine like terms: x + -1x = 0
-4x = 0

Divide each side by '-4'.
x = 0

Simplifying
x = 0

See similar equations:

| -4m-7(6m-4)= | | (7x-4)/5=0 | | 2(12/7)-5= | | -5y^2+8y-3=0 | | 16z+5z=-3 | | 10+11(x)=87 | | 3k^2-9k+5=0 | | (w/5)=20 | | 7z-(2z-8)=-2 | | (X/-2)=(-9) | | (2x-5)=(9x+7) | | 6(1-1x)=11x-2(1x+2) | | 3v^2-8v-5=0 | | (x+1)(x+1)=(x+1)(x+1) | | -3=x/3 | | 7-3x=173 | | (6x-4)-8=12 | | -3=-4+5a-4a | | 7t^2-5t-6=0 | | 16x+3=9x+73 | | -5*a+(-5*b)=5 | | -5/8x=-60 | | ((m^(1/5))/((m^(4/5))(m^-(4)))=m^(a/b) | | 8d^2+6d+1=0 | | 5(.5-3)+3(.5+3)=2(.5)-3 | | 8u^2-9u-3=0 | | 3x^3+33x^2+90x= | | 2m^2+4m+2=0 | | 3x^3+6x=4x^2+8 | | x+2x+2= | | 6(1x-1x)=11x-2(x+2) | | 7.2-3y=5 |

Equations solver categories